Performance Model for MRC Receivers with Adaptive Modulation and Coding in Rayleigh Fading Correlated Channels with Imperfect CSIT - Robles, Ramiro (2015)
This paper presents a performance model of the packet reception process in a wireless link with one antenna transmitter and a multiple-antenna maximum-ratio combining (MRC) receiver. The objective is to address the performance evaluation of multiple antenna systems enabled with adaptive modulation and coding (AMC). Two main assumptions are used: 1) Rayleigh fading correlated channels, and 2) imperfect (outdated) channel state information at the transmitter side (CSIT). The results presented here suggest that spatial correlation not always affects the performance of the MRC receiver: at low signal-to-noise ratio (SNR), correlation can improve performance rather than degrading it. By contrast, at high SNR, correlation is found to always degrade performance. At high SNR, correlation tends to worse the degrading effects of imperfect CSIT, particularly when the number of antennas increases. Imperfect CSIT causes errors in the assignment of MCSs, thus reducing throughput performance. These errors become more evident at high SNR, particularly when the values of branch correlation and the number of antennas increase.